2011
DOI: 10.1177/1742715011416894
|View full text |Cite
|
Sign up to set email alerts
|

The impossibility of the ‘true self’ of authentic leadership

Abstract: 'Authentic leadership' is increasingly influential, with its promise to eliminate, and thus surpass, the weaknesses of previous models of leadership. This article uses object relations theory to argue, firstly, that authentic leadership as an indication of a leader's true self is impossible and, secondly, that attempts at its implementation could lead to destructive dynamics within organizations. The authentic leadership model refuses to acknowledge the imperfections of individuals and despite its attestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
163
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(175 citation statements)
references
References 39 publications
(64 reference statements)
6
163
4
2
Order By: Relevance
“…Only in recent years has critical analysis exposed the tensions inherent in the concept of authenticity (Ford and Harding, 2011;Ladkin and Spiller, 2013). Existential examinations in particular question the literature's essentialist treatment of authenticity as a trait that leaders can possess or acquire (Algera and Lips-Wiersma, 2012;Lawler and Ashman, 2012).…”
Section: Authentic Leadership and Gendermentioning
confidence: 99%
“…Only in recent years has critical analysis exposed the tensions inherent in the concept of authenticity (Ford and Harding, 2011;Ladkin and Spiller, 2013). Existential examinations in particular question the literature's essentialist treatment of authenticity as a trait that leaders can possess or acquire (Algera and Lips-Wiersma, 2012;Lawler and Ashman, 2012).…”
Section: Authentic Leadership and Gendermentioning
confidence: 99%
“…These findings are of interest, however, the construct of authentic leadership has been criticized for its broad definitions its possible overlap with other positive forms of leadership such as transformational and ethical leadership, its loose interpretation of the philosophical works that are used as its theoretical foundation, such as Heidegger's (1962) notion of "resoluteness", as well as its favoring a collective self at the expense of the individual self and subjectivity. Concerns have also been raised regarding the validity and generalizability of existing measures (e.g., Ford & Harding, 2011;Gardiner, 2011;Gardner et al, 2011). Eagly (2005) criticized the one-sided perspective of existing authentic leadership models and suggested that authenticity must be acknowledged by followers for it to produce positive outcomes, naming this two-sided concept relational authenticity.…”
Section: Behavioral Perspectivesmentioning
confidence: 99%
“…Seeking authenticity is a process in which the self continuously transforms through compromises regarding social norms and standards (Heidegger, ; Sartre, ). In concordance, the transformation processes of true selves in relation to their social contexts are important perspectives that are represented in the leadership literature as well (Ford & Harding, ; Shaw, ). Some literature on authentic leadership suggests people do have a fixed authentic self that needs to be found and emphasized in one's leadership orientation (Avolio & Gardner, ; Bass & Steidlmeier, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, an implicit suggestion does not imply that the same authors believe the premise is true. There is no a priori reason to assume that emphasizing one's authenticity (whether fixed or perpetually constructed) leads to good behavior (Algera & Lips‐Wiersma, ; Ford & Harding, ; Nyberg & Sveningsson, ). In addition, the notion of good behavior is in itself problematic, as behavior in complex settings is rarely purely right or wrong (Lawler & Ashman, ) and what is right or wrong depends on the observer's perspective.…”
Section: Literature Reviewmentioning
confidence: 99%